Teaching Implicature Through Video Edited Clips in ESL Listening Classes - Susi Damaiyanti (Jurnal As-Salam, 2016)
This article is aim at reporting the teaching of pragmatic competence as part of communicative competence to enhance the students listening comprehension. It focuses on knowing how conversational implicature is taught in listening classes by using short video clips taken from some English-medium movies. Since pragmatics deals with language use in its contexts, incorporating pragmatics in EFL instructions, particularly in listening class, is imperative. This article discussions start with EFL listening comprehension process, the importance of pragmatics in EFL listening comprehension processes, pragmatic elements that make listening comprehension difficult, conversational implicature, the benefits of using movies in EFL listening instructions, and a lesson plan that incorporates implicature instruction.